Epistemic Proceduralism, Capabilities and Rights: An Approach from the Perspective of Amartya Sen - Pérez, Soledad A. (2017)
Fil: Pérez, Soledad A. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina.